การสำรวจความพร้อมของนักศึกษาระดับอาชีวศึกษาหลักสูตรการจัดการโรงแรม ต่อการเข้าสู่ตลาดแรงงาน The Exploration the Readiness of Vocational Students in Hotel Management Program to Enter Labor Market - แก้วสมบัติ, ปิ่นปินัทธ์; กวงเพ้ง, ศิริวรรณ (Chophayom Journal, 2018)
บทคัดย่อ งานวิจัยครั้งนี้ มีวัตถุประสงค์เพื่อ 1.) ระบุปัจจัยที่ส่งเสริมความพร้อมของนักศึกษาด้านความรู้และทักษะในงานสายการโรงแรม 2.) สำรวจความคิดเห็นของนักศึกษาต่อความพร้อมสู่ตลาดแรงงานอุตสาหกรรมโรงแรม และ 3.) สำรวจความคิดเห็นของบุคลากรในอุตสาหกรรมโรงแรมต่อการออกสู่ตลาดแรงงานของนักศึกษา สำรวจความพร้อมของนักศึกษาระดับอาชีวศึกษาหลักสูตรการจัดการโรงแรมต่อการสู่ตลาดแรงงาน ผู้วิจัยได้เก็บข้อมูลจากกลุ่มนักศึกษาสถาบันภาคตะวันออกเฉียงเหนือ กลุ่ม 1 ได้แก่ โดยมีวิทยาลัยอาชีวศึกษาหนองคาย, วิทยาลัยอาชีวศึกษาอุดรธานีและวิทยาลัยบริหารธุรกิจและการท่องเที่ยวอุดรธานี จำนวน 167 คน เครื่องมือวิจัยที่ใช้คือ แบบสอบถาม และการสัมภาษณ์แบบกึ่งโครงสร้างเชิงลึกกับผู้ประกอบการ จำนวน 6 คน สถิติที่ใช้ในการวิเคราะห์ข้อ มูลจากแบบสอบถาม คือ จำนวน ร้อยละ และค่าเฉลี่ย สำหรับการวิเคราะห์ข้อมูลจากการสัมภาษณ์ใช้วิธีวิเคราะห์เนื้อหา ผลการศึกษาพบว่าผลการวิจัยพบว่า 1. การจัดการเรียนการสอน และ รายวิชาในหลักสูตรของสถาบันการศึกษาเป็นปัจจัยสำคัญที่ ส่งเสริมความพร้อมของนักศึกษาด้านความรู้และทักษะวิชาชีพโรงแรม 2. นักศึกษาส่วนใหญ่พึงพอใจต่อประสบการณ์การฝึกวิชาชีพเพราะการฝึกประสบการณ์วิชาชีพเป็นการต่อยอดความรู้และทักษะวิชาชีพส่งผลให้เกิดความมั่นใจที่จะเข้าสู่ตลาดแรงงานอุตสาหกรรมโรงแรมเมื่อจบการศึกษา 3. บุคลากรโรงแรมเห็นด้วยว่านักศึกษามีความรู้และทักษะวิชาชีพที่สอดคล้องกับความต้องการของอุตสาหกรรมแต่นักศึกษาควรพัฒนาทักษะด้านภาษาต่างประเทศ และ ความกระตือรือร้นในการทำงานยิ่งขึ้นเพื่อให้สามารถแข่งขันกับแรงงานต่างชาติเมื่อเข้าสู่ตลาดแรงงานอุตสาหกรรมโรงแรมในอนาคต คำสำคัญ : นักศึกษาสถาบันอาชีวศึกษา ความพร้อมทางอาชีพ อุตสาหกรรมโรงแรม ABSTRACT This study aimed 1.) to identify factors contributing students’ knowledge and skills in hotel profession; 2.) to explore the work ready of the students entering hotel labor market and 3.) to explore the perception of hotel staff on work ready of the students entering hotel labor market. The study collected data with hotel management students from three vocational institutes located in the Northeastern Thailand, Nongkhai Vocational College, Udonthani Vocational College and Udonthani College of Business Administration and Tourism. A total of 167 questionnaire surveys were collected for quantitative data and semi-structured in-depth interview were conducted with a total of 6 representatives from students and hotel staff. Then the quantitative data was analyzed by percentage and the qualitative data was analyzed by content analysis. The study found that 1. Management of the study program and the structure of curriculum were identified by the hotel students to provide general hotel knowledge and skills related to different positions in hotel work 2. The students were mostly satisfied with their work-placement and the knowledge and skills which students learned at the institutes were relevant and practical in working in the industry. Work-placement also gives students confident to enter hotel industry after their graduation. 3. Hotel staff suggested that most students of hotel program had general knowledge and basic skills relevant to the industry. However, they should express more enthusiastic to learn and improve their language skills to be able to compete with foreigner worker in the hotel labor market in the future. Keywords : vocational student, work ready, hotel industry